Risks of citrus marketing in Lattakia Governorate - رزوق, صقاء; غسان يعقوب,; وائل حبيب , (Latakia University Journal -Biological Sciences Series, 2023)
The study mainly aimed at identifying the risks of citrus marketing in Lattakia Governorate. The analytical descriptive approach was used, and a set of methods including reliance on secondary data through books and scientific publications, and primary through a questionnaire designed based on previous studies. The research community included farmers, administrative and technical workers, decision-makers (working in the operating committee), government employees, and shop owners in Al-Hal market in Lattakia city to demonstrate the risks of citrus marketing. It was taken and distributed to (150) farms, (143) were recovered from them, and (140) was a valid questionnaire. For analysis. The results of the study showed that one of the risks of citrus marketing in Lattakia governorate is the fluctuation of prices, since the wholesale price is generally high during the first period of harvest, and begins to decrease gradually with the increase in supply in the markets. Then their prices rise again at the end of the season when their availability decreases; where the sample of farmers included in the study showed that one of the marketing risks citrus suffers from is the lack of demand for citrus products in the local market. Citrus marketing needs several stages to reach the final distribution outlets.